The correct name in Knowltonia for an iconic southern African species earlier known as Anemone tenuifolia and A. capensis (Ranunculaceae) - Mosyakin, S.L. (Український ботанічний журнал, 2018)
Following recent molecular phylogenetic findings and subsequent proposals on re-circumscription of genera earlier subsumed under Anemone sensu lato (Ranunculaceae), the genus Knowltonia is accepted here in an expanded circumscription, including both dry-fruited and fleshy-fruited African species, plus some American taxa (including those earlier treated in genera Oreithales and Barneoudia), and the Tasmanian species K. crassifolia. Nomenclature of the well-known southern African dry-fruited species earlier accepted mainly under the names Anemone capensis and A. tenuifolia is discussed. The correct name of that species in Knowltonia is K. tenuifolia (L.f.) Mosyakin, comb. nov. (= Atragene tenuifolia L.f., Anemone tenuifolia (L.f.) DC.; incl. Atragene capensis L., Anemone capensis (L.) Lam., Knowltonia pulsatilloides Christenh. & Byng, etc.). It is also demonstrated that the name Anemone capensis proposed by Lamarck should be treated as a nomenclatural combination with the basionym Atragene capensis (Art. 41.4 of the ICN), not as a name of a new taxon. Taxonomic and nomenclatural implications of that conclusion are discussed. In particular, if treated in Anemone sensu lato, the correct name of this species should be Anemone capensis (L.) Lam., not A. tenuifolia (L.f.) DC. If two leaf morphs are accepted as two different species of Knowltonia, the names K. tenuifolia (with more finely dissected, triternate leaves) and K. pulsatilloides (with biternate leaves and cuneate segments) can be used; however, the species rank for these morphs should not be recommended at our present state of knowledge. Відповідно до результатів недавніх молекулярно-філогенетичних досліджень та подальших пропозицій щодо перегляду меж родів, що раніше здебільшого включалися до Anemone sensu lato (Ranunculaceae), рід Knowltonia визнається тут у розширеному обсязі, включно з африканськими видами з сухими і ягодоподібними плодами, а також деякими американськими таксонами (у тому числі тими, які раніше розглядалися у родах Oreithales і Barneoudia) і тасманійським видом K. crassifolia. Розглянуто проблеми номенклатури широко відомого південноафриканського виду, що раніше наводився переважно як Anemone capensis і A. tenuifolia. Правильна назва цього виду в роді Knowltonia – K. tenuifolia (L.f.) Mosyakin, comb. nov. (= Atragene tenuifolia L.f., Anemone tenuifolia (L.f.) DC.; incl. Atragene capensis L., Anemone capensis (L.) Lam., Knowltonia pulsatilloides Christenh. & Byng, etc.). Також показано, що назва Anemone capensis, запропонована Ламарком, має розглядатися як номенклатурна комбінація з базіонімом Atragene capensis (стаття 41.4 МКН), а не як новий вид. Обговорюються таксономічні і номенклатурні наслідки цього висновку. Зокрема, правильною назвою цього виду в разі включення його в рід Anemone sensu lato є Anemone capensis (L.) Lam., а не A. tenuifolia (L.f.) DC. Якщо два морфотипи, що розрізняються за формою листків, приймаються як два різних види роду Knowltonia, то для них можуть бути використані назви K. tenuifolia і K. pulsatilloides. Проте, ранг виду для цих таксонів не рекомендовано. В соответствии с результатами недавних молекулярно-филогенетических исследований и последующими предложениями по пересмотру границ родов, ранее часто включаемых в Anemone sensu lato (Ranunculaceae), род Knowltonia признается здесь в расширенном объеме, включая африканские виды с сухими и ягодовидными плодами, а также некоторые американские таксоны (включая те, которые ранее рассматривались в родах Oreithales и Barneoudia) и тасманийский вид K. crassifolia. Рассмотрены вопросы номенклатуры широко известного южноафриканского вида, ранее приводимого в основном под названиями Anemone capensis и A. tenuifolia. Правильное название этого вида в роде Knowltonia – K. tenuifolia (L.f.) Mosyakin, comb. nov. (= Atragene tenuifolia L.f., Anemone tenuifolia (L.f.) DC.; incl. Atragene capensis L., Anemone capensis (L.) Lam., Knowltonia pulsatilloides Christenh. & Byng, etc.). Также показано, что название Anemone capensis, предложенное Ламарком, должно рассматриваться как номенклатурная комбинация с базионимом Atragene capensis (статья 41.4 МКН), а не как новый вид. Обсуждаются таксономические и номенклатурные следствия из этого вывода. В частности, правильным названием этого вида в случае включения его в род Anemone sensu lato является Anemone capensis (L.) Lam., а не A. tenuifolia (L.f.) DC. Если два морфотипа, различающиеся по форме листьев, принимаются как два разных вида рода Knowltonia, то для них могут быть использованы названия K. tenuifolia и K. pulsatilloides, но ранг вида для этих таксонов не рекомендуется.